On the problem of Lessepsian migrations of zooplanktonic organisms - KOVALEV, A.V. (Mediterranean Marine Science, 2006)
The scientific evidence accumulated on the migrations that zooplankton make from the Red Sea to the Mediterranean through the Suez Canal was analyzed. A conclusion was reached that some of the zooplankton, e.g. copepods Pontellina plumata, Calocalanus pavoninus, Arietellus pavoninus, reported in the literature as immigrants from the Red Sea, may in fact come from the Atlantic. The assumption is based on the fact that these organisms occur both in the eastern and the western Mediterranean. They inhabit the Atlantic Ocean, the Gibraltar Strait and the adjoining seawater, but are absent from the Suez Canal. It can be presumed that some zooplankton species widespread in the world ocean entered the Mediterranean Sea through the Gibraltar Strait and the Suez Canal.